Principle of Justice in Compensation for Disputes Due to Breach of Murabahah Contract - Nury Khoiril Jamil; Dyah Ochtorina Susanti; Rahmadi Indra Tektona (Universitas Islam Negeri Alauddin Makassar, 2025)
Contract default often occurs, as a result the creditor demands compensation from the debtor through the religious court instrument, the murabahah contract as a sharia contract which in fact implements sharia principles has fundamental differences related to compensation. The difference lies in the calculation of compensation only taking into account the original losses suffered and not the loss of future profits. The study focuses on two legal issues, namely the characteristics of compensation and the suitability of the application of compensation cases with the principle of justice in murabahah contract default disputes. This study is a normative legal study with a statutory, conceptual and case approach. The results show that sharia principle compensation has special characteristics, namely the value of compensation is calculated from real losses and does not depend on total future profits. In several cases of this study, the mandated sharia principles often do not become the legal basis for judges in deciding cases of compensation for default so that the principle of justice is not achieved.